Design of Drop Forged Rivetless Chain for Conveyor - Lu Jianfu; Lou Jianjun; Lou Yi; Jiang Haiming (Jixie chuandong)
The detailed elaboration of main technical conditions and the main dimension parameters of drop forged rivetless for conveyors chains is carriedout. The data processing method for the one-way extreme value parameter in the standards ASME B29. 22-2001 is given. Some important parameters not specified in the standards are obtained by dimensional chain calculation or strength calculation methods,and the main dimension tolerance is given. Meanwhile,according to the use of the characteristics and the use of different operating conditions of the chain,the selection of different materials and heat treatment requirements for chain part are recommended,and the strength checking formula for the inner link,the outer link and pin are given.